Shatavari supplementation during eight weeks of resistance training increases training load, enhances skeletal muscle contractility and alters the skeletal muscle proteome in older women - Greed, Elsa; Pritchard, Jack; Struszczak, Lauren; Bozbaş, Esra; Ek, Georgia; Acheson, Jordan; Winney, Ben; Qadir, Aaliyah; Wong, Karl Ka-Lam; Bowtell, Joanna; O’Leary, Mary (Frontiers in Nutrition, 2025)
IntroductionShatavari is a herbal dietary supplement that may increase skeletal muscle strength in younger and older adults. Shatavari contains compounds with both estradiol-like and antioxidant properties, which could enhance muscle function. Postmenopausal women may derive the greatest benefit, as estrogen deficiency adversely impacts skeletal muscle function. However, mechanistic insights are limited and the effects of shatavari on muscle function require further characterization.MethodsIn this randomized, double-blind trial, 17 young (23 ± 5 yr) and 22 older (63 ± 5 yr) women completed an 8-week leg resistance training programme. They consumed either a placebo or shatavari (1000 mg/d, equivalent to 26,500 mg/d fresh weight) supplement throughout. Pre and post training, measures of leg strength, neuromuscular function and vastus lateralis (VL) biopsies were obtained. Tandem-mass-tagged VL proteomic analyses were performed. Data were analyzed using a differential expression (Reactome) approach.ResultsShatavari supplementation increased 8-week training load in older women (leg press repetitions completed, p = 0.049, ηp2 = 0.198; maximum weight lifted each week, p = 0.03, ηp2 = 0.386; ANCOVA). There was no effect of shatavari on muscle strength post-training. VL half relaxation time was shortened post-training in older women supplemented with shatavari (post-training change: shatavari −11.74 ± 11.93%, placebo 0.42 ± 14.73%, p = 0.021; ANCOVA). Shatavari supplementation diminished the expression of extracellular matrix proteins in both cohorts. Expression of proteins related to striated muscle contraction, transcription and translation were decreased by shatavari supplementation in older women.DiscussionThese novel observations support the notion that shatavari supplementation confers resistance to neuromuscular fatigue in older women. This could ameliorate sarcopenic declines in skeletal muscle function.